الأمن السيبراني كركيزة لتعزيز الاقتصاد الرقمي في الجزائر: فرص وتحديات - بن عطاء الله، صبرينة; زين، يونس (University Of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى تحليل الأمن السيبراني كركيزة لتعزيز الاقتصاد الرقمي في الجزائر، من خلال استكشاف التحديات التقنية والقانونية التي تواجه هذا المجال والفرص الاقتصادية المحتملة الناتجة عن تحسينه. تناولت الدراسة الوضع الحالي للبنية التحتية للأمن السيبراني في الجزائر، مع مقارنته بالتجارب الدولية الناجحة. اعتمدت الدراسة على المنهج الوصفي التحليلي لتقديم رؤية شاملة عن المشكلات والحلول الممكنة. من النتائج المتحصل عليها، تم تحديد فجوات واضحة في التشريعات والتقنيات المستخدمة، مما يؤثر سلباً على جذب الاستثمارات وزيادة الثقة في البيئة الرقمية. كما أظهرت النتائج أن تحسين الأمن السيبراني يمكن أن يسهم في خلق فرص عمل جديدة وزيادة الاستثمارات الأجنبية، مما يدعم التنمية المستدامة في البلاد. تسعى المداخلة إلى تقديم توصيات عملية لتحسين الأمن السيبراني وتعزيز دوره في الاقتصاد الرقمي الجزائري. Abstract: This study aims to analyze cybersecurity as a pillar for enhancing the digital economy in Algeria by exploring the technical and legal challenges facing this field and the potential economic opportunities resulting from its improvement. The study addresses the current state of cybersecurity infrastructure in Algeria, comparing it to successful international experiences. It adopts a descriptive analytical approach to provide a comprehensive view of the issues and possible solutions. The results obtained identified clear gaps in the legislation and technologies used, negatively affecting the attraction of investments and increasing trust in the digital environment. The findings also indicated that improving cybersecurity could contribute to creating new job opportunities and increasing foreign investments, thereby supporting sustainable development in the country. The intervention seeks to provide practical recommendations to enhance cybersecurity and strengthen its role in the Algerian digital economy.
Cybersecurity as a Pillar for Enhancing the Digital Economy in Algeria: Opportunities and Challenges
مداخلة
Keywords: الأمن السيبراني; الاقتصاد الرقمي; التحديات الرقمية; الاستثمارات الأجنبية; التنمية المستدامة; Cybersecurity; Digital Economy; Digital Challenges; Foreign Investments; Sustainable Development